2020
DOI: 10.1101/2020.05.29.124024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brachyury controlsCionanotochord fate as part of a feedforward network and not as a unitary master regulator

Abstract: The notochord is a defining feature of the chordates. The transcription factor Brachyury (Bra) is a key regulator of notochord fate but here we show that it is not a unitary master regulator in the model chordate Ciona. Ectopic Bra expression only partially reprograms other cell types to a notochord-like transcriptional profile and a subset of notochord-enriched genes are unaffected by CRISPR Bra disruption. We identify Foxa.a and Mnx as potential co-regulators and find that combinatorial cocktails are more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
2
7
0
Order By: Relevance
“…There is very little overlap between the genes differentially expressed in the notochord at the 64-cell stage and those induced by ectopic expression of Brachyury in other studies (Figure 6 B) [73,74], suggesting that these earliest differentially expressed genes may be expressed in parallel to, and not downstream of Brachyury We found that the most common pattern was for a gene to be upregulated with respect to the parental state in one cell type while not changing in the sibling. All possible combinations were observed, however, and there were a surprising number of differentially expressed genes that were upregulated in both sibling cell types as compared to the parental cell type, but to varying extents.…”
Section: Some Fgf Dependent Cell Types Are Not Transfated To Sibling mentioning
confidence: 49%
See 3 more Smart Citations
“…There is very little overlap between the genes differentially expressed in the notochord at the 64-cell stage and those induced by ectopic expression of Brachyury in other studies (Figure 6 B) [73,74], suggesting that these earliest differentially expressed genes may be expressed in parallel to, and not downstream of Brachyury We found that the most common pattern was for a gene to be upregulated with respect to the parental state in one cell type while not changing in the sibling. All possible combinations were observed, however, and there were a surprising number of differentially expressed genes that were upregulated in both sibling cell types as compared to the parental cell type, but to varying extents.…”
Section: Some Fgf Dependent Cell Types Are Not Transfated To Sibling mentioning
confidence: 49%
“…The hourglass metaphor is an apt way to think about the establishment of new transcriptional states, but note that we are not making reference to the concept of the phylotypic stage where an hourglass metaphor has also been widely used [84]. [71,73]. We also found that Zic becomes enriched in primary notochord compared to its A-line neural sibling cells.…”
Section: Ciona Superenhancers?mentioning
confidence: 79%
See 2 more Smart Citations
“…Bra expression requires both the transcription factor Zic-r.b as well as active FGF signaling mediated by Ets family transcription factors (Yagi et al, 2004, Imai et al, 2006. These interactions are likely direct because mutation of predicted Zic and Ets binding sites in both the Proximal (Reeves and Shimai et al, 2020) and Distal (Farley et al, 2016) enhancers abrogates Bra expression. Essential Zic and Ets sites have also been identified in the Bra enhancer in the stolidobranch ascidian Halocynthia (Matsumoto et al, 2007).…”
Section: Qualitative Responses To U0126mentioning
confidence: 99%